Consumers' willingness to pay for organic rice: Insights from a non-hypothetical experiment in Indonesia - Michael Grimm; Nathalie Luck; Franziska Steinhübel (Australian Journal of Agricultural and Resource Economics, 2023)
As in many high-income countries, there is increasing awareness towards organic farming in many low- and middle-income countries. Sustained local demand is an essential requirement for further adoption of organic farming by smallholders, who typically have only limited access to export markets. Until now, only few studies have explored the local willingness to pay (WTP) for organic products in low- and middle-income countries in real purchase situations. This paper analyses the consumers' WTP for organic rice in urban and suburban Indonesia using an incentive-compatible auction based on the Becker–DeGroot–Marschak (BDM) approach. We further study the effect of income and a randomised information treatment about the benefits of organic food on respondents' WTP. Estimates suggest that respondents are willing to pay an average price premium of 20% compared with what they paid for conventional rice outside our experiment. However, our results also indicate that raising consumers' WTP further is complex. Showing participants a video about health or, alternatively, environmental benefits of organic food was not effective in further raising WTP. The results can be used as a basis for the design of alternative awareness measures to increase knowledge, interest and demand for organic food.
Keywords: 330; BDM; Indonesia; organic food; rice; willingness to pay